2020
DOI: 10.1021/acs.iecr.9b05605
|View full text |Cite
|
Sign up to set email alerts
|

Solar-Powered Rankine Cycle Assisted by an Innovative Calcium Looping Process as an Energy Storage System

Abstract: Solar energy is an intermittent resource, and thus an energy storage system is required for practical applications of the collected solar irradiance. This work deals with the integration of a thermo-chemical energy storage (TCES) system based on the calcium looping (CaL) process with a concentrated solar tower power (CSP) plant. The objective of this work is the integration of a conventional 320 MWe Rankine cycle with a direct calcination for energy harvesting. Particularly, this work addresses the use of CO 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…In addition, we supposed that the CaO sorbent deactivates at a large number of carbonation/calcination cycles. The CaO conversion is set at 70% (Chen et al, 2012), and the make-up flow is considered negligible, as reported elsewhere (Cannone et al, 2020).…”
Section: Methods and Equationsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, we supposed that the CaO sorbent deactivates at a large number of carbonation/calcination cycles. The CaO conversion is set at 70% (Chen et al, 2012), and the make-up flow is considered negligible, as reported elsewhere (Cannone et al, 2020).…”
Section: Methods and Equationsmentioning
confidence: 99%
“…The s-CO 2 Brayton cycle is integrated into the STP, replacing the current water-steam Rankine cycle analyzed in our previous work (Cannone et al, 2020) and the air Brayton cycle (Bryner et al, 2016). The CO 2 acts as heat transfer fluid and the working fluid as well.…”
Section: Power Island: S-co 2 Brayton Cyclementioning
confidence: 99%
See 1 more Smart Citation
“…Several of them have demonstrated attractive performances for TCES application, such as CaO/CaCO 3 , SrO/SrCO 3 or BaO/BaCO 3 [33]. Calcium-Looping (CaL) technology in particular, coupled with CSP, is being thoroughly studied for adaptation to TCES power plant (Equation ( 2)) [3,12,[34][35][36][37][38]. This reversible cycle requires operating temperatures between 850 and 950 • C.…”
Section: Tces Systems Based On Carbonatesmentioning
confidence: 99%
“…The majority of data available for post-combustion capture plants are based on MEA solvents. Several technologies have been developed for post-combustion processes (e.g., Calcium Looping [30,31] and membrane separation [Section 3.4]). Although they offer a future reduction of capture costs, they have not yet been developed for large capture plants.…”
mentioning
confidence: 99%